2019
DOI: 10.1111/cid.12876
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the relationship between Altmetric score and literature citations in the Implantology literature

Abstract: Background The influence of research has long been studied using citations and impact factors (IFs). Electronic media is changing how people interact with the scientific literature. There are few investigations into these trends. Purpose To explore whether Altmetrics correlate with traditional bibliometrics in the Implantology literature. Materials and Methods Five Implantology journals with the highest IF and the 10 most highly‐cited articles within those journals from 2013 to 2016 were reviewed. Altmetric sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
5
26
1
Order By: Relevance
“…A previous study analyzed all dental studies (Kolahi & Khazaei, 2018), and the mean AAS was 3.7 and 4.1 for clinical trials and reviews, respectively. A recent study analyzed the ten most-cited articles in five journals and showed lower AAS in oral implantology (Warren, Patel, & Boyd, 2019).…”
Section: Loe and Social Impactmentioning
confidence: 99%
“…A previous study analyzed all dental studies (Kolahi & Khazaei, 2018), and the mean AAS was 3.7 and 4.1 for clinical trials and reviews, respectively. A recent study analyzed the ten most-cited articles in five journals and showed lower AAS in oral implantology (Warren, Patel, & Boyd, 2019).…”
Section: Loe and Social Impactmentioning
confidence: 99%
“…Comparing the result of Kolahi et al with ours, the difference in time between the two reports should be considered, given the extreme speed of web data flow. According to what was reported in implant dentistry literature, the AAS displayed a nine-fold increase comparing the top-cited journals in 2013 and 2016 [18]. A difference of as little as 1 year could result in a tremendous change in AAS value.…”
Section: Discussionmentioning
confidence: 81%
“…Altmetric claims to use a specific algorithm to limit the effect of such misconducts by tracking down artificial patterns of attention or detecting social media automation tools [10]. The very low number of patents in the studied period could indicate a sort of disconnection between orthodontic research and the industry in contrast to the findings in periodontics, endodontics, and implant dentistry [10,18,23].…”
Section: Discussionmentioning
confidence: 99%
“…In broader areas of medicine, such as critical care medicine, prior research suggests a moderately positive correlation between traditional citation methods and Altmetrics (Lehane & Black, 2020). However, no significant correlation between citation count and Altmetric score has been noted in endodontic research (Kolahi et al, 2020), and oral implantology research (Warren, Patel, & Boyd, 2020), although it is noteworthy Altmetric scores were low in these studies due to the specialized subject area.…”
Section: Introductionmentioning
confidence: 97%